Pra studi KelayakanProduksi Keragenan Setengah Jadi - A Surjaprijana (Balai Besar Kimia dan Kemasan, 1989)
A prae feasibility study of semi-refined carrageenan production has been carried out. The cost analyses of a semi-refined carrageenan mill with the production capacity of 300 ton per year, besed on the selling price of Rp. 7.500,-/kg seen to be profitable.